Bidentate Ru(II)‐NC Complexes as Catalysts for α‐Alkylation of Unactivated Amides and Esters. Issue 19 (18th September 2019) - Gong, Dawei; Hu, Bowen; Yang, Weiwei; Chen, Dafa
Abstract: Five Ru(II)‐NC complexes were tested as catalysts for α ‐alkylation of unactivated amides using alcohols as alkylating agents, and complex (C5 H4 N)‐(C6 H4 )RuCl(CO)(PPh3 )2 (1 ) showed the highest activity. With 0.5 mol% catalyst loading, a series of α ‐alkylated amides were isolated at 80 °C within 6 hours. Furthermore, under similar conditions, complex 1 was also active for α ‐alkylation of unactivated esters with alcohols, and the reaction time was shortened to 1.5 hours. The catalytic performance of 1 is comparable to the best reported catalyst. Abstract : Alkylation under mild conditions : A bidentate Ru(II)‐NC complex is highly active for α ‐alkylation of unactivated amides and esters. The reactions were performed with low catalyst loading (0.5 mol%) under milder conditions (80 °C) for only a few hours. Twenty‐eight substrates were suitable for such transformations, and the reactions exhibited excellent conversions and functional group tolerance.